2016
DOI: 10.1186/s12948-016-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Mastocytosis and systemic sclerosis: a clinical association

Abstract: BackgroundSystemic sclerosis (SSc) is a complex autoimmune disease characterized by vascular alterations and autoimmune activation leading to widespread organ fibrosis. At the early stage of disease when organ involvement and extent of disease are emerging, mast cells may have some role, as implied by both symptoms and histologic evidence.Case presentationA female patient diagnosed with cutaneous mastocytosis experienced the onset of systemic sclerosis after 15 years followed by the switch of mastocytosis to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Mast cell infiltration was detected from lip biopsy in very early stages of SSc and preceded the onset of skin changes and more recently cutaneous mastocytosis was found to precede the onset of SSc in a 36‐year‐old woman suggesting that mast cells may play an early role in the onset of SSc. Mast cell infiltration has also been detected late in the development of SSc and in a subset of SSc patients with localized scleroderma‐like lesions .…”
Section: Mast Cellsmentioning
confidence: 96%
“…Mast cell infiltration was detected from lip biopsy in very early stages of SSc and preceded the onset of skin changes and more recently cutaneous mastocytosis was found to precede the onset of SSc in a 36‐year‐old woman suggesting that mast cells may play an early role in the onset of SSc. Mast cell infiltration has also been detected late in the development of SSc and in a subset of SSc patients with localized scleroderma‐like lesions .…”
Section: Mast Cellsmentioning
confidence: 96%
“…These pathways are regulated at the post-translational level by modification of ubiquitination and mutations of ubiquitination enzyme genes have been found in scleroderma patients ( Long et al, 2018 ). Furthermore, a role for mast cells, innate immune cells commonly known to play a key role in anaphylaxis ( Toniato et al, 2017 ; Maurer and Pucillo, 2018 ), has also been found in the initiation of the sclerotic process ( Bagnato et al, 2016 ; Bradding and Pejler, 2018 ). At the early stages of scleroderma, when mast cells accumulate in a specific tissue such as the dermis, forming an inflammatory infiltrate, they start to interact with fibroblasts ( Willenborg et al, 2014 ; Gurung et al, 2019 ).…”
Section: Organ Fibrosis Emt and Possible Anti-emt Therapeutic Stratementioning
confidence: 99%
“…Mast cells have been detected in SSc tissues and can exhibit pro-fibrotic manifestations. Elevated infiltration of mast cells has been found in various SSc tissues including the skin and salivary glands [ 34 , 35 , 36 ]. Mast cell infiltration has been correlated with more severe disease phenotypes.…”
Section: The Role Of Immune Cells In Ssc-related Inflammation and Fib...mentioning
confidence: 99%